The association between HIV infection, disability and lifestyle activity among middle-aged and older adults: an analytical cross-sectional study in Ivory Coast (the VIRAGE study) - Pierre Debeaudrap; Nadine Etoundi; Joseph Tegbe; Nelly Assoumou; Zelica Dialo; Aristophane Tanon; Charlotte Bernard; Fabrice Bonnet; Hortense Aka; Patrick Coffie (BMC, 2024)
Abstract Introduction People living with HIV (PLWH) live longer and face new health challenges resulting from the confluence of chronic HIV infection and the natural effect of aging and comorbidities. However, there is a dearth of information on the long-term impact of HIV infection on the health and wellbeing of PLWH in sub-Saharan Africa. This research aimed to fill this gap by reporting on physical, functional and social outcomes among PLWH treated at a referral center in Abidjan, Ivory Coast, and comparing them with those of a control group. Methods Body composition, functional capacity, sarcopenia, limitations in daily activities and social participation were assessed among 300 PLWH (aged ≥ 30 years) and 200 uninfected adults of similar age and sex. The associations between these outcomes and participants' socioeconomic characteristics, HIV history and physical activity level were assessed using generalized additive models adjusted for age and sex. Results The median age was 51 years, and the median antiretroviral therapy duration was 15 years. Compared to controls, PLWH reported higher levels of physical activity (p < 0.0001). They had a lower muscle index (adjusted p < 0.0001) and grip strength (adjusted p < 0.0001) but achieved similar performance on the 6-min walk test (6MWT, p = 0.2). Among PLWH, physical activity level was positively associated with better performance in the 6MWT (p = 0.006) and greater hand grip strength (p = 0.04). The difference in physical performance according to the level of physical activity appeared mainly after the age of 60. PLWH reported similar rates of activity limitations (p = 0.8), lower depression levels and greater scores for social functioning (p = 0.02). Conclusion In this study, PLWH achieved high levels of physical activity, which may explain why they maintained good physical performance and social functioning despite having a higher risk of sarcopenia. These results have important implications for resource-limited health systems and show avenues for chronic care models. Trial registration This study was registered on the ClinicalTrials.gov website (NCT05199831, first registration the 20/01/2022).